A decision support system to aid the calculation of the cost of the post-harvest processing of coffee - Santos, Rafael Vargas Mesquita; Vieira, Henrique Duarte; Borém, Flávio Meira; Isquierdo, Eder Pedroza (Coffee Science - ISSN 1984-3909, 2014)
Various computer programs were developed to calculate the cost of the coffee harvest. However, few address the costs of coffee in its post-harvest stage. This study was aimed to develop a system for calculating the cost of the coffee postharvest to facilitate decision making regarding the most cost-effective post-harvest processes. Thirty-four farmers in southern Minas Gerais state answered a questionnaire designed to validate this system. The use of a decision support system showed that the simulated costs in the post-harvest stage were not statistically different from the costs informed by the representatives of the selected farms.